External beam radiation and brachytherapy boost at different facilities is associated with increased treatment delays in cervical cancer. Issue 10 (14th September 2020) - Li, Richard; Germino, Elizabeth; Horne, Zachary D; Vargo, John A; Chen, Yi-Jen; Glaser, Scott
Abstract : Introduction: Due to variation in facility expertise and capabilities, patients commonly complete external beam radiation therapy at one facility and brachytherapy boost at another. We evaluated the association of external beam radiation therapy and brachytherapy at the same facility versus different facilities with treatment delays and survival. Methods: Patients receiving definitive external beam radiation therapy and brachytherapy for non-metastatic cervical cancer from 2004 to 2015 were identified in the National Cancer Database. Treatment delays were classified based on published thresholds: a course of >56 days was considered delayed, >65 days moderately delayed, and >77 days severely delayed. Fisher's exact test and logistic regression were used to evaluate the association of same facility versus different facilities with treatment delays and predictors of same facility versus different facility treatment. Results: We identified 23 911 patients meeting the inclusion criteria at a median follow-up of 39.7 months (IQR 21.0–72.6 months), with 17 391 patients (72.7%) receiving same facility treatment and 6520 patients (27.3%) receiving different facility treatment. Any treatment delay was found in 49.3% of same facility treatments versus 51.9% of different facility treatments (p<0.001); moderate or worse delays in 24.8% of same facility versus 29.4% of different facility treatments (p<0.001); severe treatment delays in 11.3% of same facility versus 15.5% of different facility treatments (p<0.001). Receipt of same facility versus different facility treatment was independently associated with treatment delays (OR 1.28, 95% CI 1.20 to 1.37; p<0.001). Both treatment delays, particularly moderate delays (HR 1.20, 95% CI 1.13 to 1.28; p<0.001) and severe delays (HR 1.32, 95% CI 1.24 to 1.41; p<0.001), and different facility treatments (HR 1.11, 95% CI 1.06 to 1.16; p<0.001) were associated with worse survival. Conclusions: Delivery of external beam radiation therapy and brachytherapy at different facilities was associated with treatment delays and worse survival. Our findings underscore the importance of care coordination in cervical cancer management.